1995
DOI: 10.1097/00006254-199506000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Cerclage

Abstract: The treatment of patients with cervical incompetence presenting with advanced cervical changes in the second trimester remains a challenge to every obstetrician. Cerclage operation may be the only hope for prolonging gestation until fetal viability is reached. A retrospective study on so-called emergency cervical cerclage in 20 patients with supposed cervical incompetence in the late second trimester is presented, together with a review of comparable studies published between 1980 and 1992. It is concluded tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 34 publications
2
39
0
4
Order By: Relevance
“…However, it seems reasonable to use a short course of broad-spectrum prophylactic antibiotics as in any other surgical procedure involving the vagina. On the other hand, tocolysis is not used systematically as some authors [7,9,16,17] do not use tocolysis at all while others use indomethacin [5,14,18] or ritodrine [19,20,21]. Finally, amniocentesis prior to the indication of cerclage has been suggested by Mays et al [22] who showed that selection of women according to the results of the amniocentesis improved perinatal results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it seems reasonable to use a short course of broad-spectrum prophylactic antibiotics as in any other surgical procedure involving the vagina. On the other hand, tocolysis is not used systematically as some authors [7,9,16,17] do not use tocolysis at all while others use indomethacin [5,14,18] or ritodrine [19,20,21]. Finally, amniocentesis prior to the indication of cerclage has been suggested by Mays et al [22] who showed that selection of women according to the results of the amniocentesis improved perinatal results.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the technique are heterogeneous, with some authors using only the McDonald technique [9,10,18,21,23] and others using the McDondald or the Shirodkar technique depending on operator experience [6,8,20,22]. In the review by Aarts et al [16], the authors found no evidence that the technique used influences the prolongation or the outcome of pregnancy. Therefore, in our protocol, the cervical technique was left to the discretion of the operator.…”
Section: Discussionmentioning
confidence: 99%
“…In unseren Fällen wurden alle Patientinnen mit intravenöser Tokololyse, Lungenreifung, Bettruhe und Antibiotika therapiert. In der Literatur finden sich Berichte, welche die [15,16].…”
Section: Diskussionunclassified
“…35 The prognosis is in¯uenced by the gestational age at the time of suture placement. 36 Orr 37 reported the technique of using a Foley catheter balloon with the tip cut off as a counterpressure to the bulging bag of membranes. This is pushed into the lower uterus and a McDonald stitch placed round the cervix.…”
Section: Emergency Cervical Cerclagementioning
confidence: 99%